Engaging the Christian scriptures : an introduction to the Bible - Arterbury, Andrew E.; W.H. Bellinger; Derek S. Dodson (Grand Rapids, Michigan : Baker Academic, 2014)
This readable, affordable, and faith-friendly introduction to the Bible aids students as they engage in their first informed reading of the biblical text in an academic setting. The authors, who have significant undergraduate teaching experience, approach the Christian Scriptures from historical, literary, and theological perspectives. The book is designed for a one-semester course and is meant to be read alongside the biblical text, enabling students to become educated readers of the Bible. In the process, it introduces critical perspectives and approaches without undermining the theological claims found in the Christian Scriptures. The book includes text boxes, illustrations, maps, and suggestions for further reading.
Suggested reading.
Includes bibliographical references and index.
Keywords: Bible -- Introductions